Structural insights into the binding of zoledronic acid with RANKL via computational simulations - Wang, Ruijie; Zhang, Wenjie; Ma, Hailong; Zou, Duohong; Zhang, Zhiyuan; Wang, Shaoyi (Frontiers in Molecular Biosciences, 2022)
Zoledronic acid (ZOL) inhibits receptor activator of nuclear factor-κB ligand (RANKL) and reduces bone turnover. This plays an important role in the development of bisphosphonate-related osteonecrosis of the jaw (BRONJ). Previous reports have shown that ZOL binds to the enzyme farnesyl pyrophosphate synthase (FPPS) to block its activity. However, the mechanism of action of ZOL and its interaction with RANKL is still unclear. In this study, we confirmed that ZOL significantly suppressed the bone remodeling in ZOL-treated rats, investigated whether ZOL could bind to RANKL and examined the interactions between these molecules at the atomic level. Surface plasmon resonance (SPR) assay was performed to validate that ZOL could directly bind to RANKL in a dose dependent manner, and the equilibrium constant was calculated (KD= 2.28 × 10−4 M). Then, we used molecular docking simulation to predict the binding site and analyze the binding characteristics of ZOL and RANKL. Through molecular dynamics simulation, we confirmed the stable binding between ZOL and RANKL and observed their dynamic interactions over time. Binding free energy calculations and its decomposition were conducted to obtain the binding free energy −70.67 ± 2.62 kJ/mol for the RANKL–ZOL complex. We identified the key residues of RANKL in the binding region, and these included Tyr217(A), Val277(A), Gly278(A), Val277(B), Gly278(B), and Tyr215(C). Taken together, our results demonstrated the direct interaction between ZOL and RANKL, indicating that the pharmacological action of ZOL might be closely related to RANKL. The design of novel small molecules targeting RANKL might reduce the occurrence of BRONJ.